SNAPTIMED study: does the Scottish and Newcastle Antiemetic Protocol achieve timely intervention and management from the emergency department to discharge for paracetamol poisoning?. Issue 3 (18th August 2022) - Humphries, Christopher; Roberts, Georgina; Taheem, Anjeli; Abdel Kader, Hashem; Kidd, Rebecca; Smith, Jason
Abstract : Background: This study aimed to establish whether the modified 12-hour Scottish and Newcastle Antiemetic Protocol (SNAP) for paracetamol poisoning is associated with improvement in hospital length of stay (LoS), as well as to validate the performance of the protocol for the prevention of anaphylactoid reactions and total infusion duration. Methods: Retrospective chart review from 25 March 2019 to 25 September 2020. Patients aged 16 or older with a diagnosis of suspected or confirmed paracetamol overdose were included in the analysis if they received treatment for paracetamol poisoning, and the protocol used could be identified. Data were collected for LoS, number of extended treatment infusions used and evidence of anaphylactoid reaction. Results: 1167 records were assessed for eligibility, and 294 were included for analysis. Use of the SNAP was associated with a statistically significant reduction in LoS of −8.8 hours (95% CI −12.6 to −2.0), and a reduced risk of anaphylactoid reaction (Number Needed to Treat=10). Conclusion: In this retrospective study, use of the SNAP reduced the duration of inpatient admissions and rate of anaphylactoid reactions.